2022
DOI: 10.1093/icb/icac095
|View full text |Cite
|
Sign up to set email alerts
|

EcoPhysioMechanics: Integrating Energetics and Biomechanics to Understand Fish Locomotion under Climate Change

Abstract: Ecological physiologists and biomechanists have investigated swimming performance in a diversity of fishes; however, the connection between form, function, and energetics of locomotion has been rarely evaluated in the same system and under climate change scenarios. In this perspective, I argue that working within the framework of “EcoPhysioMechanics,” i.e. integrating energetics and biomechanics tools, to measure locomotor performance and behavior under different abiotic factors, improves our understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…The positioning of the entrances of fish passage facilities in unsuitable locations has the potential to disorient fish. Fish tend to adopt the most efficient swimming mode during upstream migration to maintain optimal energy expenditure (Di Santo, 2022; Di Santo et al, 2017). Therefore, the optimal velocities identified in this study (Figure 11b) can be applied to predict fish migration routes in rivers using CFD (Computational fliud dynamics) modeling (Liao et al, 2022; Silva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positioning of the entrances of fish passage facilities in unsuitable locations has the potential to disorient fish. Fish tend to adopt the most efficient swimming mode during upstream migration to maintain optimal energy expenditure (Di Santo, 2022; Di Santo et al, 2017). Therefore, the optimal velocities identified in this study (Figure 11b) can be applied to predict fish migration routes in rivers using CFD (Computational fliud dynamics) modeling (Liao et al, 2022; Silva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, these three swimming speeds were too macroscopic for fish studies, which could miss some key points about fish swimming patterns. Some studies have shown that the kinematic consumption of fish shows a “j”‐ or “U”‐shaped curve from low to high flow velocity (Di Santo, 2022; Di Santo et al, 2017). This indicates that there may be two swimming patterns between the induced and critical swimming speeds.…”
Section: Introductionmentioning
confidence: 99%